Relationship between inferior wall of maxillary sinus and maxillary posterior teeth using cone-beam computed tomography in healthy and chronic periodontitis patients - Alkananda Chand; Bhagyashree Ronghe; Girish Byakod; Alok Ashok Lathi; Sangeeta Muglikar (Wolters Kluwer Medknow Publications, 2017)
Background: For dental implant planning in maxillary posterior region, it is essential to know their relationship with maxillary sinus. Maxillary posterior teeth affected by chronic periodontitis usually have a poor prognosis, ultimately leading to tooth loss. Following tooth loss, significant bone resorption occurs resulting in compromised remaining bone support for dental implant placement. Aim: The study aims to determine the relationship between inferior wall of maxillary sinus and the root apices of maxillary posterior teeth. Materials and Methods: The study sample consisted of cone-beam computed tomography images of 150 patients. Vertical distance between inferior wall of maxillary sinus and root apices and furcation area of maxillary posterior teeth as well as crest of the edentulous ridge were measured in periodontally healthy individuals (Group 1), chronic periodontitis patients (Group 2), and in patients with edentulous maxillary posterior region (Group 3). The data were analyzed using one-way analysis of variance and Tukey's test to compare mean distances between groups and molars. Results: There was a significant difference in mean distances between Group 1 (3.067 ± 1.600), Group 2 (1.602 ± 0.536) and Group 3 (1.279 ± 0.476) (P = 0.00001) and between mean distances of four sites (7.101, 0.932, 0.903, and 0.402 mm) (P ≤ 0.05). There was no significant difference in mean distances between the first and second molars (2.1469; 2.0996) (P = 0.787). Conclusion: For planning of dental implant placement in maxillary posterior region, the clinician should consider the vertical relationship between maxillary sinus floor and root apices of maxillary molars.